Are children and young people more susceptible to the newer strains of SARS-CoV-2 than earlier ones? Current evidences - Bashar, Mohammad Abu; Begam, Nazia (International Journal of Scientific Reports, 2021)
The clinical impact of the new SARS-CoV-2 lineage B.1.1.7 on children and young people (aged 18 years or younger) regarding acute respiratory COVID-19 is yet to be fully defined. Some media reports of increases in admissions to hospital and more serious illnesses in children and young people have resulted in Public chaos and panic and implicated the B.1.1.7 variant as a cause of more pathogenic infection within this group. The aim of the study was to present the currently available evidence of increase susceptibility of the children and young people COVID-19 towards the B.1.1.7 strain of SARS-CoV-2.